Costs and benefits of reproducing under unfavorable conditions: an integrated view of ecological and physiological constraints in a cerrado shrub - Silveira, Fernando A. O.; Santos, Jean C.; Franceschinelli, Edivani V.; Morellato, Leonor Patrícia Cerdeira [UNESP]; Fernandes, G. Wilson (Springer, 2015)
Disentangling the relative importance of biotic and abiotic constraints in plant reproduction is a major challenge in reproductive ecology. Here, we tested the 'resource limitation hypothesis'that predicts a high-level ovule abortion under resource scarcity; the 'flowering displacement hypothesis'that predicts low levels of pollen limitation driven by relaxed competition for pollinators; and the 'herbivory escape hypothesis'that predicts low impact by natural enemies during unfavorable conditions. We followed reproductive phenology, measured the seasonal variation in resource abundance, and calculated initial ovule budgets to estimate the relative importance of each limiting factor on final reproductive output. Ovule fate was determined of ovules in different positions within the pods, and a germination experiment was conducted to identify bottlenecks at the germination stage. Despite marked decreases in resource availability during the dry season, reproduction consistently occurred during mid-to-late dry season. Destruction by natural enemies and abortion were the most likely ovule fates, with only 2.2 % of flower buds converted into ripe fruits. Ovule fates were not random along fruit positions, with higher likelihood of well-formed seeds in fruit tips and higher likelihood of ovule abortion and non-fertilized ovules near the fruit bases. The benefits derived from flowering displacement to the dry season include reduced competition for pollinators and synchronization of seedling establishment with the onset of the rainy season. However, we found no support for the herbivory escape hypothesis. We argue that a cost-benefit approach is a useful framework to understand the evolutionary ecology of phenological strategies in seasonal environments.
Keywords: Cerrado; Ovule fate; Phenology; Pollen limitation; Pre-dispersal seed predation; Resource limitation